Pemanfaatan Konservasi Tradisional Harimau Sumatera sebagai Potensi Pengembangan Bahan Ajar Biologi - Ovi Zurah Mei; I Gusti Putu Suryadarma (Postgraduate, University of Mataram, 2023)
Indigenous communities have long had an unwritten norm system that regulates the protection of forests and biodiversity inside. Customary law has the potential to be developed as a source of learning biology. Therefore, the purpose of this study is to find out the values of traditional conservation of the Sumatran tiger which can be used as a source of developing biology teaching materials based on local wisdom. The method used in this research is a systematic literature review. Based on the results of the study, obtained results regarding the identification of Sumatran tiger, threats, and forms of conservation in the natural habitat of the Sumatran tiger. Based on the Curriculum 2013, the relevance of this study is linked into basic competencies 3.2 and 4.2 regarding distribution, threat analysis, and conservation efforts of biodiversity for the grade of 10-th of high school.Â The material is also included in the learning outcomes of the Merdeka Curriculum phase E regarding understanding and process skills analyzing interactions between ecosystem components and efforts to conserve biodiversity. These material resources can be developed into a module-based on local culture to be studied independently by students